Οι ρόλοι που υιοθετούν οι μαθητές/τριες όταν γίνονται μάρτυρες εκφοφισμού στο σχολείο και η σχέση τους με τις πεποιθήσεις ενσυναίσθησης και αυτεπάρκειας - Lihnou, Konstantina; Antonopoulou, Ekaterini (Preschool and Primary Education, 2016)
Introduction: Pupils who observe bullying can adopt a number of different roles: (1) assistants, who join the bullies and bully the victim, (2) reinforcers, who support the bullies by cheering, (3) outsiders, who remain uninvolved with the bullying and (4) defenders, who try to help the victim. However, relevant findings have shown that bystanders seldom act as defenders of the victims. Furthermore, research on bystander behaviour in bullying has shown that defender behaviour is related, among others, to empathy, anti-bullying attitudes, high social status and self-efficacy. Purpose of the study: The present paper sought to examine the participant roles that primary school pupils undertake when they are bystanders (assistants, reinforces, outsiders, defenders) during school bullying events. Furthermore, it examines the degree to which empathy and self-efficacy may influence pupils’ bystander behaviours. Method (participants, design & materials): Three hundred and sixty seven primary school pupils (172 boys and 195 girls) with mean age 10.53 years old (s.d.= 0.71) responded to the Greek version of three self-reported measures: a) the Participant Role Scale, b) the Basic Empathy Scale and c) Children’s Self-Efficacy Scale. Results: The results showed that the participant role with the highest frequency among the participating children is the one of the defender who takes the side of the victim comforting and supporting them. Furthermore, pupils’ self-efficacy and empathy were found to be moderate but significant factors in predicting the development of defending behavior among bystanders. Implications & conclusions: The present findings have important educational and psychological implications. They suggest that defender behaviours could be enhanced by encouraging the development of pupil self-efficacy and empathy within the school context.